2020
DOI: 10.1177/0021955x20912201
|View full text |Cite
|
Sign up to set email alerts
|

Thermoplastic polyurethane foams: From autoclave batch foaming to bead foam extrusion

Abstract: Two ester-based and one ether-based thermoplastic polyurethane grades have been used to produce thermoplastic polyurethane foams. The foaming process comprised pressure-induced batch foaming, foam extrusion, and bead foam extrusion by using an underwater granulator. Foam density and morphological properties, such as cell size, cell size distribution, and cell density, were measured through different analytical methods. Through autoclave batch foaming a minimum cell size of 10 µm and density of 202 kg/m3 is obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…Nevertheless, the ratio A h / A c showed a lower interconnection when 0.1 equiv of PMHS is used compared to 0.5 equiv. Compared to PU flexible foams, the obtained foams with 0.5 equivalent of blowing agent showed similar characteristics in terms of pore size and distribution. Moreover the density was also similar to that of PU foams . However, the foam using 0.1 equiv of PMHS showed a lower cell size.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…Nevertheless, the ratio A h / A c showed a lower interconnection when 0.1 equiv of PMHS is used compared to 0.5 equiv. Compared to PU flexible foams, the obtained foams with 0.5 equivalent of blowing agent showed similar characteristics in terms of pore size and distribution. Moreover the density was also similar to that of PU foams . However, the foam using 0.1 equiv of PMHS showed a lower cell size.…”
Section: Resultsmentioning
confidence: 75%
“…60−62 Moreover the density was also similar to that of PU foams. 63 However, the foam using 0.1 equiv of PMHS showed a lower cell size. For all the foams, the density was highly reduced with the use of blowing agent (Table 3).…”
Section: Resultsmentioning
confidence: 98%
“…Today two different production methods are used 31 : a discontinuous suspension and a continuous foam extrusion process. 32 The suspension process is a batch foaming process, where TPU pellets were impregnated with a blowing agent (n-butane 30,33 or carbon dioxide [34][35][36] ) under high pressure. Depressurizing of the systems leads to expansion.…”
Section: Advanced Mechanical Propertiesmentioning
confidence: 99%
“…Their results show that the foams produced by batch foaming had a higher cell density and a smaller cell size than foam extrusion and bead foaming. 12 Qu and his coworkers investigated batch foaming of a blend of polystyrene and TPU. They reported that the solubility of CO 2 and the rheological properties were enhanced by blending PS with TPU, and a bimodal cellular structure was formed by blending TPU with PS as a dispersed domain.…”
Section: Introductionmentioning
confidence: 99%
“…Shabani and coworkers conducted batch foaming, foam extrusion, and bead foam of TPU and compared the cell structures of the resulting foams. Their results show that the foams produced by batch foaming had a higher cell density and a smaller cell size than foam extrusion and bead foaming 12 . Qu and his coworkers investigated batch foaming of a blend of polystyrene and TPU.…”
Section: Introductionmentioning
confidence: 99%